Genetic diversity in oocyte donors used in in vitro bovine embryo production programs in Brazil - Ortiz Vega, Wilder Hernando; Quirino, Celia Raquel; Bartholazzi Junior, Aylton; Slade Oliveira, Clara; Varella Serapião, Raquel; Gomes David, Caroline Marçal; Silva Rua, Miguel Alejandro; Barros de Freitas, Ana Carolina (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Current reproductive management of bovine elite populations involves the use of assisted reproductive technologies (ARTs), aiming to obtain the greatest genetic gain. However, inadequate use of ARTs may lead to loss of genetic diversity in the offspring. Objective: To assess the genetic diversity in elite female cattle populations used in commercial in vitro embryo production. Methods: Using genetic and ecological approaches for the study of populations based on microsatellite markers, we assessed the genetic diversity between and within populations of cows used in commercial in vitro embryo production programs in Brazil. Results: Endogamy within populations varied from zero to 9.1%, while heterozygosity between populations (FST) was <0.05 in the different population interactions. AMOVA showed 1% variation between populations, 8% between individuals and 91% within individuals. The dimensionality reduction method utilized indicated a lack of structure in the populations analyzed, identifying two main clusters in the three populations. Conclusions: Low genetic diversity between cow populations associated with commercial programs of in vitro embryo production in Brazil was evidenced. Variable levels of endogamy within the populations were observed. Approaches of population genetics as well as ecological diversity can be implemented to more thoroughly estimate genetic diversity in livestock populations.